An Internet-based program for depression using activity and physiological sensors: efficacy, expectations, satisfaction, and ease of use - Botella C; Mira A; Moragrega I; García-Palacios A; Bretón-López J; Castilla D; Riera López del Amo A; Soler C; Molinari G; Quero S; Guillén V; Miralles I; et al. (Neuropsychiatric Disease and Treatment)
Cristina Botella,1,2 Adriana Mira,1 Inés Moragrega,2,3 Azucena García-Palacios,1,2 Juana Bretón-López,1,2 Diana Castilla,1,2 Antonio Riera López del Amo,1 Carla Soler,1 Guadalupe Molinari,1 Soledad Quero,1,2 Verónica Guillén-Botella,2,3 Ignacio Miralles,1,2 Sara Nebot,1 Berenice Serrano,1,2 Dennis Majoe,4 Mariano Alcañiz,2,5 Rosa María Baños2,31Department of Basic, Clinical Psychology and Psychobiology, Universitat Jaume, Castellón, Spain; 2CIBER Physiopathology of Obesity and Nutrition, CIBERobn, Instituto de Salud Carlos III, Santiago de Compostela, Spain; 3Department of Personality, Evaluation and Psychological Treatment, Universidad de Valencia, Valencia, Spain; 4Native Systems Institute, ETH Zurich, Zurich, Switzerland; 5Human-Centered Technology Institute, Universidad Politécnica de Valencia, Valencia, Spain Purpose: Computerized cognitive behavioral therapy (CCBT) has been shown to be efficacious. Moreover, CCBT can be enhanced by using physiological and activity sensors, but there is no evidence about the acceptability of all these tools. The objective of this study is to examine the efficacy, expectations, satisfaction, and ease of use of an Internet-based CCBT program for preventing depression, with and without sensors (electroencephalography, electrocardiograhpy ECG, and actigraphy), in a high-risk population (unemployed men).Patients and methods: Sixty participants at risk of depression (unemployed men) were randomly assigned to three experimental conditions: 1) intervention program (N=22), 2) intervention program plus sensors (N=19), and 3) control group (N=19). Participants completed depression, anxiety, positive and negative affect, and perceived stress measures. Furthermore, they also completed the measures for expectation, satisfaction, and the ease of use of the program.Results: Results showed that the two intervention groups improved significantly more than the control group on the clinical variables, and the improvements were greater in the group that used sensors than in the group that did not use them. Furthermore, participants in both intervention groups scored high on expectations and satisfaction with the CCBT program (with and without sensors). The mean score for usability was 88 out of 100 (standard deviation =12.32). No significant differences were found between groups on any of these variables.Conclusion: This is the first study to analyze the efficacy, expectations, satisfaction, and ease of use of an Internet-based program using physiological and activity sensors. These results suggest that an Internet program for depression with or without physiological and activity sensors is effective, satisfactory, and easy to use. Keywords: depression, ease of use, efficacy, Internet, sensors, satisfaction